Mending the fractures : creating a multi-stakeholder framework for building shared purpose in unconventional oil and gas - Jones, Jamie; Bryant, Peter; Snyder, Charlotte (London : Kellogg School of Management, 2018)
A large energy company purchased leasing rights for developing unconventional gas resources in British Columbia. However, the province failed to secure to consult with the local indigenous population before awarding the lease. Maria Paque, the senior vice president of resource development must now meet with the tribal chief in order to gain permission for the fracking or to go ahead or the project will be scrapped.
Originally Published InJones, J., Bryant, P., & Snyder, C. (2018). Mending the fractures: Creating a multi-stakeholder framework for building shared purpose in unconventional oil and gas. 5-314-502. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gas industry -- Environmental aspects -- British Columbia; Energy development -- Environmental aspects -- British Columbia; Renewable energy sources -- British Columbia; Oil-shale industry -- Environmental aspects -- British Columbia